A Randomized Open Clinical Study of the Atherosclerosis Treatment Information Video Effect on Adherence to Long-Term Therapy in Patients with Cardiovascular Diseases - Yu. V. Bulaeva; E. A. Naumova; O. N. Semenova; T. V. Kanaeva; K. A. Popov; А. R. Tyapayeva (Столичная издательская компания, 2021)
Aim. Study the effect of a study video, which was created by researchers and devoted to the atherosclerosis development and the effect of statin therapy on atherosclerotic plaque, on adherence to long-term therapy in patients with high or very high risk of cardiovascular complications.Material and methods. 120 patients admitted to hospital with cardiovascular diseases were included in the study. Patients were randomized into 2 groups: in the main group (n=60), the information video edited by the researchers was shown to patients on the eve of discharge, in addition to a printed brochure on lifestyle and diet modification, and in the control group (n=60), patients were given only a standard brochure. The motivating video shows the damage to the cardiovascular system by the atherosclerotic process and the beneficial effect on the body of constant intake of statins. After 1 and 3 months after discharge from the hospital, telephone calls were made, after which the patients had to visit the center for an objective examination by a researcher and control of laboratory parameters. After 1 month, 110 patients visited the center, after 3 months, 98 respondents visited the center.Results. The group with the information video demonstration noted more frequent adherence to medical recommendations compared to the control: after 1 month, 52 (96%) patients continued treatment versus 48 (86%) patients, 3 months after discharge 48 (96%) patients continued treatment versus 38 (79%) patients (p<0.05). After 1 month, 38 (70%) patients in the intervention group continued taking statins versus 29 (43%) respondents in the control group (p<0.05), 3 months after discharge, 40 (80%) patients in the intervention group continued to take statins versus 33 (69%) control patients (p<0.09).Conclusion. Demonstration of a motivating video about the effect of statins on the atherosclerosis course increases patient adherence to medicinal therapy, including adherence to statins.